2006
DOI: 10.1111/j.1524-4725.2005.31021
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma Protuberans of the Forehead and Scalp with Involvement of the Outer Calvarial Plate: Multistaged Repair with the Use of Skin Expanders

Abstract: Multistaged repair of the face is a viable alternative surgical approach to preserve facial contours and minimize distortion in the treatment of DFSP. This case illustrates the degree of complexity that the treatment of DFSP may involve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…This is a reassuring finding considering that 50% of DFSP recurrences are observed within the first year and 80% within the first 3 years. 4 The low recurrence rates demonstrated with MMS in our patient population and in previous reports compare favorably to those of traditional surgery with reported marginal recurrence rates of 20% to 50%. 4,9 DFSP is known to have extensive subclinical spread with 3-cm surgical margins yielding recurrence rates of up to 20% 9 and reports of greater than 10 cm of lesion spread beyond the clinical border.…”
Section: Dermatofibrosarcoma Protuberanssupporting
confidence: 83%
See 1 more Smart Citation
“…This is a reassuring finding considering that 50% of DFSP recurrences are observed within the first year and 80% within the first 3 years. 4 The low recurrence rates demonstrated with MMS in our patient population and in previous reports compare favorably to those of traditional surgery with reported marginal recurrence rates of 20% to 50%. 4,9 DFSP is known to have extensive subclinical spread with 3-cm surgical margins yielding recurrence rates of up to 20% 9 and reports of greater than 10 cm of lesion spread beyond the clinical border.…”
Section: Dermatofibrosarcoma Protuberanssupporting
confidence: 83%
“…4 The low recurrence rates demonstrated with MMS in our patient population and in previous reports compare favorably to those of traditional surgery with reported marginal recurrence rates of 20% to 50%. 4,9 DFSP is known to have extensive subclinical spread with 3-cm surgical margins yielding recurrence rates of up to 20% 9 and reports of greater than 10 cm of lesion spread beyond the clinical border. 7 Ratner and associates 7 reported that standard wide excision with a width of 1 cm would leave residual tumor in 70.7% of tumors; 2 cm would leave tumor in 39.7%; 3 cm would leave tumor in 15.5%; and 5 cm would leave tumor in 5.2%.…”
Section: Dermatofibrosarcoma Protuberanssupporting
confidence: 83%
“…Most cases in the literature and at RPCI required complex closure, including mucocutaneous flaps, free flaps, and pedicle flaps with or without the use of split‐thickness skin grafts. For restoration of the patient's normal hairline, some authors have suggested the possibility of using scalp expansion 19,20 . Dermatologic surgeons must be prepared to undertake advanced reconstruction of their defects with the help of a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…DFSP on the scalp can cause erosion of the bone and even fatal invasion of the brain. [5][6][7]17,18 For these patients, an invasive surgical procedure will be required with removal of the affected periosteum and calvarial plate. Closure of these defects can be challenging and necessitates a multidisciplinary approach by the Mohs surgeon, plastic surgeons, and neurosurgeons.…”
Section: General Aspects Of Dermatofibrosarcoma Protuberansmentioning
confidence: 99%